Level of Oxidative Stress Markers in Peri-Implant CrevicularFluid and Their Correlation with Clinical Parameters - Mahvash Mousavi Jazi; Hamid Reza Sadeghi Pour Rodsari; Faezeh Mirmiran (Tehran University of Medical Sciences, 2016)
Objective: Increased levels of oxidative stress markers in periodontitis have been reported by recent studies. Malondialdehyde (MDA) and superoxide dismutase (SOD) are both in- creased during oxidative stress. The aim of this study was to detect and measure the level of oxidative stress markers in peri-implant crevicular fluid (PICF). Their correlation with peri-implant clinical parameters was investigated as well. Materials and Methods: PICF samples of 50 dental implants were collected in 31 pa- tients. Peri-implant clinical parameters including probing pocket depth (PPD), gingival index (GI) and bleeding on probing (BOP) were recorded. Levels of oxidative stress markers including MDA, SOD and total antioxidant capacity (TAC) in PICF were deter- mined. Results:  Twenty  four  implants  showed  signs  of  inflammation  and  26  implants  had healthy  peri-implant tissues. MDA and TAC were seen in all samples, but SOD was not detected around 31 implants. The differences between the two groups with respect to the levels of MDA, TAC and SOD in PICF, were not statistically significant (P> 0.05).  In addition, significant positive correlations were observed between PPD and TAC and MDA level (P<0.05). Conclusion: Significant correlations exist between PPD and level of MDA and TAC. Moreover, level of oxidative stress markers (MDA, SOD and TAC) in PICF does not sig- nificantly change in peri-implantitis compared to healthy implants. Measuring these mark- ers in PICF does not seem to be helpful for discrimination of peri-implant health and dis- ease status.